La reutilización de la información del sector público. Aproximación al contenido de la propuesta de directiva 2002 - Ramos Simón, L. Fernando (Revista General de Información y Documentación, 2003)
The information in digital support gathered by the different organisms of the public sector is of great interest to companies as a market research information source and to the public at large as an element of transparency and democratic participation. Many western countries have considered revising their relationship with the citizenry in this new electronic environment. To this end, the European Union has proposed the regulation of the re-use of this public information by means of a directive in which homogeneous criteria are established for the whole of the community’s territory (COM/2002/0207; DOCE C 227, 24-9-2002 y DOCE, L 345, 31-XII-2003).